Febrile temperatures induce cytoadherence of ring-stage Plasmodium falciparum-infected erythrocytes - Rachanee Udomsangpetch (2018)
In falciparum malaria, the malaria parasite induces changes at the infected red blood cell surface that lead to adherence to vascular endothelium and other red blood cells. As a result, the more mature stages of Plasmodium falciparum are sequestered in the microvasculature and cause vital organ dysfunction, whereas the ring stages circulate in the blood stream. Malaria is characterized by fever. We have studied the effect of febrile temperatures on the cytoadherence in vitro of P. falciparum-infected erythrocytes. Freshly obtained ring-stage-infected red blood cells from 10 patients with acute falciparum malaria did not adhere to the principle vascular adherence receptors CD36 or intercellular adhesion molecule-1 (ICAM-1). However, after a brief period of heating to 40°, all ring-infected red blood cells adhered to CD36, and some isolates adhered to ICAM-1, whereas controls incubated at 37°C did not. Heating to 40°C accelerated cytoadherence and doubled the maximum cytoadherence observed (P < 0.01). Erythrocytes infected by ring-stages of the ICAM-1 binding clone A4var also did not cytoadhere at 37°C, but after heating to febrile temperatures bound to both CD36 and ICAM-1. Adherence of red blood cells infected with trophozoites was also increased considerably by brief heating. The factor responsible for heat induced adherence was shown to be the parasite derived variant surface protein PfEMP-1. RNA analysis showed that levels of var mRNA did not differ between heated and unheated ring-stage parasites. Thus fever-induced adherence appeared to involve increased trafficking of PfEMP-1 to the erythrocyte membrane. Fever induced cytoadherence is likely to have important pathological consequences and may explain both clinical deterioration with fever in severe malaria and the effects of antipyretics on parasite clearance.